Chance Encounters: Rap Music as a Relational and Pedagogical Resource in Clinical Pastoral Education - Gilmore, Jeremy (The journal of pastoral care & counseling, 2018)
Music has long been regarded as a valuable tool for educators. Over the last three decades, rap music has grown to become a global phenomenon. However, due to historical and cultural factors, rap music is often underutilized in Clinical Pastoral Education. This article discusses the social significance of rap music, highlights how rap music informed my supervision of a clinical pastoral education student, and examines Chance the Rapper’s mixtape Coloring Book as a case study on the utilization of rap music as a relational and pedagogical resource in spiritual education.